A new species of Eudesis Reitter from Spain (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2025)
Eudesis hispanica sp. nov. is described. This is the second Eudesis Reitter known to occur in Spain, and the third continental European species of this blind, wingless and miniaturized endogean genus. The type material was collected by the soil washing technique in Córdoba, from the mineral soil layer on an open area with marls and limestones. For the first time the collecting sites of Eudesis are documented by a photographic material, to facilitate future efforts to find this rare and poorly known genus.